Analisis Akuntabilitas dan Efektifitas Dalam Pengelolaan Dana Desa Melalui Badan Usaha Milik Desa di Desa Ria (Studi Kasus Kecamatan Riung Barat, Kabupaten Ngada, Provinsi Nusa Tenggara Timur) - Mirawati Lompeng; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Village funds are one of the sources of budget procurement in the village for help the village community in developing the village economy besides that village funds are channeled to BUMDes because BUMDes is one of the institutions that will build and support the economy of the village community. This study aims to determine the level of accountability and effectiveness of village fund management through village-owned enterprises in West Riung District Ngada Regency. This research method uses descriptive qualitative methods using primary data and secondary data. Methods of data collection using interview and documentation techniques. Based on the results of research conducted by researchers that the accountability of village funds channeled through BUMDes financial management is not in accordance with applicable regulations while the effectiveness of village funds channeled through BUMDes has been effective because it has an impact on the community.Keywords: Accountability, effectiveness, village fund, BUMDes